2024
DOI: 10.1021/acsanm.4c00103
|View full text |Cite
|
Sign up to set email alerts
|

(CoFeMnCuNiCr)3O4 High-Entropy Oxide Nanoparticles Immobilized on Reduced Graphene Oxide as Heterogeneous Catalysts for Solvent-Free Aerobic Oxidation of Benzyl Alcohol

Seyedsaeed Mehrabi-Kalajahi,
Ahmad Ostovari Moghaddam,
Fahimeh Hadavimoghaddam
et al.

Abstract: The development of noble metal-free heterogeneous catalysts holds promise for the solvent-free and selective aerobic oxidation of organic compounds. However, the moderate activity of these catalysts under atmospheric conditions limits their industrial use. In this work, the synthesis of noble metal-free (CoFeMnCu-NiCr) 3 O 4 high-entropy oxide (HEO) nanoparticles and their grafting on reduced graphene oxide (rGO) to produce a HEO− rGO nanocomposite is detailed. X-ray diffraction (XRD), scanning electron micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…The Raman spectrum of the La­(FeCuMnMgTi)­O 3 HEO nanoparticles reveals a distinct broad asymmetric band at 493 cm –1 and a low-intensity band at 1307 cm –1 (Figure b). Moreover, the HEO showcases six main Raman bands at 125, 198, 336, 645, and 1307 cm –1 , providing compelling evidence of their consistency with similar structures . The presence of a 645 cm –1 band emphasizes the existence of distinct cubic units within the lattice structure.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…The Raman spectrum of the La­(FeCuMnMgTi)­O 3 HEO nanoparticles reveals a distinct broad asymmetric band at 493 cm –1 and a low-intensity band at 1307 cm –1 (Figure b). Moreover, the HEO showcases six main Raman bands at 125, 198, 336, 645, and 1307 cm –1 , providing compelling evidence of their consistency with similar structures . The presence of a 645 cm –1 band emphasizes the existence of distinct cubic units within the lattice structure.…”
mentioning
confidence: 75%
“…This method often uses toxic solvents and has safety concerns . To align these oxidation reactions with green chemistry, it is essential to develop milder catalytic reaction processes that eliminate the need for harmful solvents and oxidizing agents, reducing their environmental impact and improving safety and economic feasibility. , Recent studies have demonstrated that metal heterogeneous catalysts can selectively oxidize alcohols without the need for additional oxidizing agents in a solvent-free manner under mild conditions. , In this regard, the development of high-performance heterogeneous catalysts for aerobic solvent-free oxidation of benzyl alcohol to key commercial raw materials is an important topic.…”
mentioning
confidence: 99%
“…(j) Recyclability test of the HEO-rGO catalyst for the solvent-free oxidation of PhCH 2 OH. Panels (h–j) are adapted with permission from ref . Copyright 2024 American Chemical Society.…”
Section: Applicationsmentioning
confidence: 99%
“…However, Mehrabi-Kalajahi et al’s study outlined the synthesis of noble metal-free NPs composed of (CoFeMnCu-NiCr) 3 O 4 HEO and their subsequent grafting onto reduced graphene oxide (rGO) to form a HEO-rGO composite material . The HEO-rGO nanocomposites exhibited exceptional performance in the aerobic and solvent-free oxidation of PhCH 2 OH.…”
Section: Applicationsmentioning
confidence: 99%